PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN DAN NIATAN LOYALITAS PADA PEMONDOKAN MAHASISWA PERGURUAN TINGGI X - Howard S. Giam; Fahrul Riza (Business Management Journal, 2017)
Homestay or dormitory is one of primary needs student who studied far from their home town. This demand for home stay have been responding by residents around the campus by promote an empty space or room at their home to be rent. As one of strategy to expand the quality of service and generate a new income channel, campus or university have been also providing homestay for their student which used to call dormitory and it’s managed by professional management building. A tight competitiveness in this business have made the management building need to explore what factors will cause increase satisfaction and loyalty from dormitory’s tenant. This paper investigated impact of quality product and quality service to loyalty intention with satisfaction as a moderating variable among 102 tenants of student dormitory from University X. The findings was product quality wasn’t affect the satisfaction and loyalty intention, meanwhile service quality was significant at α 1%. Implication of these findings management building dormitory from University X must improve their service quality to attain loyality from tenants. Keywords: Service Quality, Product Quality, Loyalty Intention, Satisfaction